Patient satisfaction with fixed-combination bimatoprost/timolol ophthalmic solution: a survey study in patients with glaucoma in China - Sun XH; Lin M; Duan XC; Zhang C; Ming J (Patient Preference and Adherence, 2017)
Xinghuai Sun,1,2 Mingkai Lin,3 Xuanchu Duan,4 Chun Zhang,5 Jian Ming6 1Eye, Ear, Nose and Throat Hospital, Shanghai Medical College, Fudan University, Shanghai, 2Key Laboratory of Myopia, Ministry of Health (Fudan University), and Shanghai Key Laboratory of Visual Impairment and Restoration (Fudan University), Shanghai, 3Zhongshan Ophthalmic Center, Guangzhou, 4The Second Xiangya Hospital of Central South University, Changsha, 5Peking University Third Hospital, Beijing, 6Allergan plc, Shanghai, People’s Republic of China Background: Poor adherence to treatment is a problem in glaucoma, and patient dissatisfaction with topical glaucoma medication is a barrier to adherence. The objective of this study was to evaluate glaucoma patients’ satisfaction with fixed-combination bimatoprost/timolol ophthalmic solution (BTFC). Methods: This observational, multicenter study was conducted in China in adults with glaucoma treated with BTFC for 1–3 months. Five hundred patients answered a questionnaire concerning their demographic characteristics, history of glaucoma and topical glaucoma treatment, and use of BTFC. The primary endpoint was patient satisfaction with BTFC assessed on a 10-point scale (1= very dissatisfied, 10= very satisfied).Results: Patients received BTFC alone (65%) or with other treatments (35%), most commonly a carbonic anhydrase inhibitor. Most patients (87%) used BTFC as a replacement for other medication, usually a β-blocker or prostaglandin analog; 13% received BTFC as add-on treatment. Key reasons for initiating BTFC therapy were poor efficacy of previous treatment (72% of patients) and side effects of previous treatment (32% of patients). Most patients agreed or very much agreed that BTFC provided better control of intraocular pressure (85% of patients), had a simpler administration (87% of patients), and was associated with better tolerance and comfort (82% of patients) compared with their previous treatment. Mean satisfaction scores were significantly higher for BTFC than for previous treatments among all patients (7.8 versus 6.0; P<0.0001) and within patient subgroups based on demographic characteristics, pattern of BTFC use, and previous treatment.Conclusion: Patients were highly satisfied with BTFC used alone or concomitantly with another topical medication. Patients previously treated with a β-blocker, prostaglandin analog, carbonic anhydrase inhibitor, α-adrenergic agonist, or combination of two medications were more satisfied with BTFC than with their previous treatment. Most reported that intraocular pressure control, tolerability, and ease of administration improved with BTFC. Keywords: bimatoprost, fixed combination, glaucoma, patient compliance, timolol